El Excentrico, 1955-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
Janurary 5, 1955 [5 de enero de 1955]. Ano 5, No 5. Cover has a photo of an infant named Ernie Sanchez sitting down with a happy expression. Below is the headline, "1955 Happy New Year 1955."